Kinematics and dynamics of mechanical systems with lubricated revolute joints: the infinitely-short journal-bearing approach - Flores, Paulo (2007)
This paper deals with a methodology to assess the influence of the lubricated revolute joints in the kinematics and dynamics of mechanical systems. The existence of the clearance at revolute joints is inevitable in all mechanical systems and most of them are designed to operate with a lubricant fluid. In the present work, the infinitely-short journal-bearing approach for dynamic loads is used to evaluate the resulting hydrodynamic forces of the pressure distribution in the lubricated revolute joints. These hydrodynamic forces are then introduced into the system’s equations of motion as external applied forces. A numerical example is presented in order to demonstrate the efficiency and accuracy of the methodology and procedures adopted in this work. The numerical results point out that the existence of lubricated joint can affect the kinematics and dynamics of system.